All-dielectric Metamaterial for Electromagnetically-induced Transparency in Optical Region - Linh, Pham The; Ninh, Nguyen Thi Viet; Quang, Nguyen Dinh; Lam, Tran Tien; Ngoc, Nguyen Van; Khuyen, Bui Xuan; Hien, Nguyen Thi; Lam, Vu Dinh; Tung, Bui Son (Communications in Physics, 2020)
Metamaterial (MM) is emerging as a promising approach to manipulate electromagnetic waves, spanning from radio frequency to the optical region. In this paper, we employ an effect called electromagnetically-induced transparency (EIT) in all-dielectric MM structures to create a narrow transparent window in opaque broadband of the optical region (580-670 nm). Using dielectric materials instead of metals can mitigate the large non-radiative ohmic loss on the metal surface. The unit-cell of MM consists of Silicon (Si) bars on Silicon dioxide (SiO\(_{2}\)) substrate, in which two bars are directed horizontally and one bar is directed vertically. By changing the relative position and dimension of the Si bars, the EIT effect could be achieved. The optical properties of the proposed MM are investigated numerically using the finite difference method with commercial software Computer Simulation Technology (CST). Then, characteristic parameters of MM exhibiting EIT effect (EIT-MM), including Q-factor, group delay, are calculated to evaluate the applicability of EIT-MM to sensing and light confinement